Forward and inverse problems of electrocardiography : clinical investigations - Farina, Dmytro (Karlsruhe transactions on biomedical engineering / Ed.: Universität Karlsruhe (TH) / Institute of Biomedical Engineering, 2008)
The non-invasive reconstruction of cardiac activity can significantly improve the quality of cardiac diagnostics. Two major approaches are considered. The model-based method consists in the optimization of an electrophysiological cardiac model until the measured and simulated ECGs are similar. The inverse problem of electrocardiography is solved to compute the cardiac sources distributions from body surface potential maps. The results and their interpretation are shown for several patients.